2018
DOI: 10.3390/ijerph15081721
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Drinks Intake, Late Chronotype, and Increased Body Mass Index among Medical Students in Chongqing, China: A Multiple Mediation Model

Abstract: Background: This paper investigates the problems regarding caffeinated drinks intake, late chronotype, and increased body mass index (BMI) among medical students at a Chinese university. Methods: This cross-sectional study was conducted in 2018 with 616 medical students from Chongqing Medical University in Chongqing, China, whose information were collected by a self-reported questionnaire that included four sections: Demographic characteristics; Caffeinated drinks intake and physical state; Morningness-Evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
1
18
1
Order By: Relevance
“…The rate of evening types in this study (6.9%) is lower than in one study investigating medical college students in Chongqing, China (14.3%; Zhang et al, 2018) and another study mentioned above involving Italian and Spanish college students (24.45%; Adan & Natale, 2002). Nonetheless, the prevalence of moderate/extremely severe depressive symptoms and clinical sleep disturbances were both high (7.7% and 18.1%, respectively), especially for evening types (13.1% and 29.1%).…”
Section: Discussioncontrasting
confidence: 80%
“…The rate of evening types in this study (6.9%) is lower than in one study investigating medical college students in Chongqing, China (14.3%; Zhang et al, 2018) and another study mentioned above involving Italian and Spanish college students (24.45%; Adan & Natale, 2002). Nonetheless, the prevalence of moderate/extremely severe depressive symptoms and clinical sleep disturbances were both high (7.7% and 18.1%, respectively), especially for evening types (13.1% and 29.1%).…”
Section: Discussioncontrasting
confidence: 80%
“…of several studies suggest that compared to morning-type individuals, evening-type individuals consume more alcohol and smoke more cigarettes (Ishihara et al 1985;Randler 2008;Tran et al 2014;Whittier et al 2014) and have a higher caffeine intake (Adan 1994;Ishihara et al 1985;Mitchell and Redman 1993;Tran et al 2014;Zhang et al 2018). Penolazzi et al (2012) found that the timing of caffeine consumption is also important, and reported that morning-type individuals consume more caffeine in the morning and evening-type individuals consume more caffeine in the evening.…”
Section: Resultsmentioning
confidence: 99%
“…Total cholesterol was classi ed into ≥ 200 mg/dl and < 200 mg/dl. As Zhang's study [28], BMI was split into < 18.5 Kg/m 2 , < 24 Kg/m 2 , < 28 Kg/m 2 and ≥ 28Kg/m 2 . After referring to Arihan's research [29], BUN was divided as 0-20 mg/dl and > 20 mg/dl.…”
Section: Covariatesmentioning
confidence: 99%